2006
DOI: 10.1007/s11661-006-0129-4
|View full text |Cite
|
Sign up to set email alerts
|

Elastoplastic deformation of 316 stainless steel under tensile loading at elevated temperatures

Abstract: The response of 316 stainless steel has been examined under uniaxial tensile loading during ar ange of tests carriedo ut between 20°Ca nd 650°C. In-situ neutron diffraction was used to measure internal elastic strain in subsets of differently oriented crystallites within the polycrystal aggregate. This allowed the determination of diffraction elastic constants. Further,r esults have been compared with predictions from as lip-based elasto-plastic self-consistent model. Good agreement is obtained during both con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 28 publications
4
51
1
Order By: Relevance
“…The diffraction elastic constants (DEC) for each plane were obtained by dividing the change in applied stress by the corresponding change in lattice strain for each plane during unloading and are summarised in Table 2. The elastic moduli obtained in the current study perfectly agreed with the work conducted by Daymond and Bouchard [6]. The lattice strains relaxed with the relaxation of applied stresses linearly during creep under Z * 1.2 and Z * 10.5 and act similar to unloading process, as shown in c. Therefore, the lattice strains were found to relax the most in the elastically softest lattice plane {200} and the least in the elastically stiffest lattice plane {111} due to different grain families in crystalline materials displaying elastic anisotropies.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The diffraction elastic constants (DEC) for each plane were obtained by dividing the change in applied stress by the corresponding change in lattice strain for each plane during unloading and are summarised in Table 2. The elastic moduli obtained in the current study perfectly agreed with the work conducted by Daymond and Bouchard [6]. The lattice strains relaxed with the relaxation of applied stresses linearly during creep under Z * 1.2 and Z * 10.5 and act similar to unloading process, as shown in c. Therefore, the lattice strains were found to relax the most in the elastically softest lattice plane {200} and the least in the elastically stiffest lattice plane {111} due to different grain families in crystalline materials displaying elastic anisotropies.…”
Section: Resultssupporting
confidence: 90%
“…It is well known that when a polycrystalline material undergoes macroscopic plastic deformation, intergranular strains or stresses can be generated within grain families as a consequence of elasticplastic anisotropy at the grain scale [6][7][8][9]. Creep as a time-dependent plastic deformation can also generate intergranular strains/stresses in Type 316H austenitic stainless steel often during primary stage of the constant load creep [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Its single crystalline counterpart has shown significant elastic anisotropy (see Ledbetter, 1981). The three independent elastic constants, C 11 , C 22 , C 44 for 316H were obtained by Daymond and Bouchard (2006) from ND measurements and are adopted in the current study as shown in Table 2. The shear modulus, µ 0 at 0 K needed for the flow rule (Eqn.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…The shear modulus, µ 0 at 0 K needed for the flow rule (Eqn. 4), was obtained by extrapolating the modulus data of Daymond and Bouchard (2006) 6 M A N U S C R I P T…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation